CAFF Map No.38 - Population trends in colonies of Arctic murres Uria spp - Arctic Council , Conservation of Arctic Flora and Fauna Working Group (CAFF International Secretariat, 2001)
CAFF Map No.38 - Population trends in colonies of Arctic murres Uria spp, 2001